Answer:
x = 2
y = -2
Step-by-step explanation:
N.B. Assuming the first equation is actually 3x + 4y = -2
The elimination method is an incredibly useful tool used to save large amounts of time when working with small systems of equations.
First, set one variable in the top equation to have an equal coefficient as that same variable in the bottom equation.
3(3x + 4y) = 3(-2)
Then, you are left with this. Simply subtract the equations.
9x + 12y = -6
9x - 10y = 38
0 + 22y = -44
Then, simply solve
y = -2
9x + 20 = 38
9x = 18
x = 2
Hope it helps :) and let me know if you want me to elaborate.